The Used of Different Culture Medium Effect on The Growth Of Chlorella Sp - Diana Chilmawati (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2010)
The effort of aquaculture especially in the brackish and marine water becomes more develope,. That development cannot be separated from seeding phase. To sufficient the needed of seed, it is needed seed aquaculture by giving sufficient and quality life food, because it cannot be replace yet by the imitation food on the early of larvae seedling. One of the life food is Chlorella sp that given to zooplankton variety directly to the fish or shrimp cultivan. Therefore the Walne, Guillard’s f/2, and Erdschreiber culture mediums are suitabel medium used to phytoplankton culture.  The purpose of this research is to know the influence of medium of usage of Walne, Guillard’s f/2, and Erdschreiber on the growth of Chlorella. Also to know the best medium from those three medium on the growth of Chlorella sp the research was Laboratories experimental character. The effort scheme used is completely randomized design 3 treatments and 3 times repetitions,  Those 3 treatments are as follows: A. Walne Medium, B. Guillard’s f/2 Medium, and C. Erdschreiber Medium. The result of the research shows that the used of different culture medium effect on the growth of Chlorella sp, that is significant difference (P<0,05) on the Lag Phase time with best treatment B (0,290 days), great significant difference (P<0,01) on the specific growth rate with best treatment B (0.655). Thus on the maximum density and final density (on Log No. sel/mL) is great significant differences with best treatment B (Guillard’s f/2) each are 7.931 and 6.443. The best medium for Chlorella sp. from those three mediums used in this research is Guillard’s f/2 medium.                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                          Key Words : medium, culture, growth, Chlorella sp